The life style of glaucoma patients: a scientific rationale for basic recommendations - N. A. Bakunina; L. N. Kolesnikova (Российский офтальмологический журнал, 2022)
The review presents a literature analysis on the life style and diet habits of patients with glaucoma. The issue is relevant due to the flow of versatile information in the media, including the Internet, which offers recommendations that lack evidence and may put patients at risk. The review summarizes recent studies on nutrition that take account the factors of glaucoma pathogenesis, physical activity recommendations, the regimens of sleep and rest, possible effects of simultaneous systemic and local use of β-adrenoblockers, and other life style factors essential for patients with glaucoma.